Effects of Natural Carbon Sources and Temperature on Mycelium Cultivations of Lentinus squarrosulus (Mont.), Lentinus polychrous Lev., Pleurotus ostreatus (Jacq.ex Fr.) P. Kumm. and Volvariella volvacea (Bull.) Singer - Kupradit, Chanida; Ranok, Araya; Mangkalanan, Seksan; Khongla, Chompoonuch; Musika, Sumalee (Thai Journal of Science and Technology, 2020)
Mycelial biomass can be used as an inoculum source for mushroom production and is a suitable source to produce useful substances. Temperature and carbon sources play a role in the production of biomass and bioactive compounds of mycelium cultivation. Thus, natural carbon sources including potato, sweet potato, and taro were used in this mycelium cultivation study. The purposes of this study were to investigate the effects of carbon sources and temperature on mycelium cultivation for four edible mushrooms. The growth of Lentinus squarrosulus (Mont.), Lentinus polychrous Lev., Pleurotus ostreatus (Jacq. ex Fr.) P. Kumm. and Volvariella volvacea (Bull.) Singer in culture media with various carbon sources at different temperatures were examined for their growth based on biomass and diameter. The results indicated that potato dextrose broth (PDB) was a suitable medium for growing P. ostreatus, V. volvacea and L. squarrosulus. The optimum temperature for the mycelial growth of V. volvacea, L. squarrosulus and P. ostreatus with maximum yields of 8.47±0.26 g/L, 6.44±0.30 g/L and 3.76±0.18 g/L, respectively, was 30±2oC after 7 days of incubation using a submerged cultivation. For L. polychrous, a sweet potato dextrose broth (SPDB) was a suitable medium for mycelial production (6.16±0.69 g/L) when cultivated at 35±2oC for 7 days. For mycelia cultivation on an agar medium, the maximum mycelium colony diameter of four edible mushrooms (6-9 cm) were obtained from the taro dextrose agar (TDA) medium at 3-8 days of incubation. Therefore, TDA was suitable and efficient mediums for cultivation of the four edible mushrooms.